Analysis of Financial Characteristics of Sustainability Report: Company Size as Moderating Variable - Indana, Dina; Pangestuti, Irene Rini Demi (Research Horizon, 2024)
Environmental, social, and governance disclosure are important for corporations to enhance their performance in these areas. In Indonesia, only a few businesses produce sustainability reports. This study seeks to investigate the role of firm size in moderating the influence of profitability, liquidity, and leverage on sustainability performance as measured by ESG disclosures in non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Using the purposive sampling strategy, 61 sample companies were identified. The data was analyzed using the SEM-PLS approach and the Smart PLS 3.0 application. The findings revealed that profitability has insignificant influence but positively on ESG disclosure, whereas liquidity and leverage have a significant effect but negatively on ESG disclosure. Company size was able to moderate by increasing the effect of liquidity and leverage factors on ESG disclosure, but not profitability. The study's findings support stakeholder theory in terms of the company's attempts to develop and publicize its sustainability report.